Incidence of enamel defects on permanent canine teeth following extraction of linguoverted mandibular deciduous canine teeth in dogs - Felz, Charles L.; Arzi, Boaz; Taney, Kendall; Block, Katherine (Frontiers in Veterinary Science, 2024)
Interceptive orthodontics may be indicated in puppies exhibiting dental malocclusion with linguoverted deciduous mandibular canine teeth to alleviate pain and prevent teeth interlock, which may affect growth and development of the mandibles. Historically extraction of deciduous mandibular canine teeth has been recommended as soon as a malocclusion is identified, often as early as 6–8 weeks of age and no later than 12 weeks of age. This early surgical intervention of deciduous teeth extractions risks potential damage to the developing permanent canine teeth resulting in enamel defects often referred to as a Turner’s tooth or Turner’s hypoplasia. A search of medical records from five veterinary specialty dentistry practices was conducted to identify dogs 8–12 weeks of age who (a) underwent deciduous mandibular canine extractions for management of class 1 or class 2 malocclusion with linguoverted mandibular canine teeth, and (b) were seen for at least one recheck exam to assess for enamel defects on permanent mandibular canine teeth. Furthermore, data was collected to determine the number of dogs that required additional treatment after eruption of the permanent canine teeth due to linguoversion of the permanent canine teeth. All procedures were performed by a board-certified veterinary dentist™ or a supervised veterinary dentistry resident. Seventy-four dogs fit the inclusion criteria and had a total of 143 deciduous mandibular canine teeth extracted, out of which 13 dogs exhibited enamel defects affecting 21 permanent canine teeth. The 13 affected dogs represent a 17.5% cumulative incident rate 13/74 (95%CI 11–28%). Of all extracted teeth, 14.6% (21/143) had enamel defects affecting permanent canine teeth. Twenty-eight dogs required additional treatment to prevent the permanent mandibular canine teeth from causing trauma to the hard palate and gingiva which represented 37.8% (28/74) of all dogs in the study. Age and sex of the dog at the time of extraction were not found to be associated with the likelihood of incidence of enamel defects. This is the first reported rate of enamel defects on permanent mandibular canine teeth following extraction of deciduous mandibular canine teeth and is important to consider when advising or performing extraction of deciduous teeth in dogs.